2021
DOI: 10.1187/cbe.21-06-0153
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Student Perceptions of Instructor Talk: Alignment with Researchers’ Categorizations and Analysis of Remembered Language

Abstract: Students were asked to evaluate a stimulus set of previously recorded Instructor Talk quotes as positive or negative, and whether students could recall noncontent instructor language was investigated. Overall, students’ evaluations of Instructor Talk quotes were in alignment with researchers, and most students could recall memories of Instructor Talk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Furthermore, students may have work or caregiving responsibilities and are unable to attend out of class sessions or office hours. In addition, this type of messaging aligns with research on “negatively‐phrased instructor talk”––non‐content talk by instructors that can discourage students and are often remembered by them as negative experiences (Harrison et al, 2019; Ovid et al, 2021).…”
Section: Resultssupporting
confidence: 60%
“…Furthermore, students may have work or caregiving responsibilities and are unable to attend out of class sessions or office hours. In addition, this type of messaging aligns with research on “negatively‐phrased instructor talk”––non‐content talk by instructors that can discourage students and are often remembered by them as negative experiences (Harrison et al, 2019; Ovid et al, 2021).…”
Section: Resultssupporting
confidence: 60%
“…This study builds on prior research that characterizes how students perceive their instructor within phenomena‐based laboratory curricula (Kendall & Schussler, 2012; Ovid et al, 2021) and investigates the dynamic of instructor–student interactions during phenomena‐based investigations (Chen & Techawitthayachinda, 2021; Donnelly et al, 2014). This study provides insight into the relationship between perceptions regarding an instructor's role and student learning outcomes (RQ1) along with the importance of instructor–student interactions in cultivating a student‐centered environment (RQ2).…”
Section: Discussionmentioning
confidence: 99%
“…Further research examining Instructor Talk across multiple classroom contexts showed both positively and negatively phrased Instructor Talk has lasting impacts on students’ perceptions of the classroom environment ( Harrison et al. , 2019 ; Ovid et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%